Inflammasomes and Fibrosis - Zhang, Wen-Juan; Chen, Shu-Juan; Zhou, Shun-Chang; Wu, Su-Zhen; Wang, Hui (Frontiers in Immunology, 2021)
Fibrosis is the final common pathway of inflammatory diseases form various organs. The inflammasomes play important role in the fibrosis as innate immune receptors. There are four main members of the inflammasomes, such as NOD-like receptor protein 1 (NLRP1), NOD-like receptor protein 3 (NLRP3), NOD-like receptor C4 (NLRC4), and absent in melanoma 2 (AIM2). NLRP3 inflammasome is the widely studied. NLRP3 inflammasome is usually composed of NLRP3, ASC and pro-caspase-1. The activation pathways of inflammasome are divided into "classical" and "non-classical" pathways and the former pathway is more clear. The "classical" activation pathway of inflammasome is that the backbone protein is activated by endogenous/exogenous stimulation, leading to the formation of inflammasome. After the formation of "classic" inflammasome, pro-caspase-1 could self-activate to Caspase-1. Caspase-1 cleaves cytokine precursors into mature cytokines, which are secreted extracellularly. At present, the "non-classical" activation pathway of inflammasome has not formed a unified activation process. This article reviews the role of NLRP1, NLRP3, NLRC4, AIM2 inflammasome, Caspase-1, IL-1β, IL-18 and IL-33 in the fibrosis.